Jeffrey Gitomer's little book of leadership : - Gitomer, Jeffrey H. (John Wiley & Sons Inc., 2011)
The Little Book of Leadership combines classic style with the latest innovations to challenges the reader to self-evaluate every facet of their leadership, coaching, and communication abilities in order to better formulate what actions can be taken to improve their natural skills. Ideas and answers are provided for every challenge.